A dual biomimetic process for the selective aerobic oxidative coupling of primary amines using pyrogallol as a precatalyst. Isolation of the [5 + 2] cycloaddition redox intermediates. Issue 6 (25th February 2020) - Largeron, Martine; Deschamps, Patrick; Hammad, Karim; Fleury, Maurice-Bernard
Abstract : Low-cost pyrogallol precatalyst undergoes an oxidative self-processing step for delivering the active organocatalyst in situ through a dual biomimetic process. Abstract : A bioinspired organocatalytic cascade reaction mimicking both purpurogallin biosynthesis and copper amine oxidases (CuAOs) activity is described, at room temperature under ambient air, for the activation of the α-C–H bond of primary amines. The reaction sequence uses low-cost commercially available pyrogallol as a precatalyst which undergoes an in situ oxidative self-processing step, resulting in its conversion into natural purpurogallin, a [5 + 2] cycloaddition redox intermediate. This is further involved in the CuAOs-like transamination mechanism for producing, under single turnover, the active biomimetic organocatalyst which mediates the selective oxidative coupling of primary amines, including the non-activated substrates of CuAOs. Without any metal cocatalyst or additives, the protocol gives access to cross-coupled imines as well as 1, 2-disubstituted benzimidazoles. The isolation of not easily accessible [5 + 2] cycloaddition redox intermediates provides direct and clear evidence for the proposed dual biomimetic process.